Bihar agriculture a perspective - Bansil, P.C. (New Delhi Concept, 2011)
This book examines agricultural perspectives in Bihar and comes up with the conclusion that this State which has shown an annual growth rate of over 11 per cent in Agriculture GDP during the last 5 years, has the potential of taking its place of pride as the forerunner of Second Green Revolution. The book is divided into 14 chapters. First 7 chapters undertake a critical analysis of the present ground situation for a proper understanding of the emerging issues success stories and failures with reasons in each case. The next 4 chapters Input Management, Research and Extension, Infrastructure and Policy Framework deal with the respective issues in each case. The chapter on Development Strategy starts with SWOT analysis and is built on the PAPSL theory (Participatory Assessment and Planning for Sustainable Livelihood) developed by Prof. Chambers, Sussex University. It is interesting to observe that Bihar was more or less at the same level as Punjab in agricultural development till the late sixties and has today gone far behind. Factors responsible for development of Punjab agriculture and those of China and India (under Looking Beyond) are carefully examined. About the Author P C Bansil heads the Techno Economic Research Institute, New Delhi, founded by him in 1984. He belongs to the first batch of Indian Economic Service and has worked with FAO for about 15 years in Sri Lanka, Thailand, Rome, Zambia and Libya. He has authored 30 books, besides a large number of reports and papers prepared for various Governments. He has published over 400 papers in specialized technical journals. His work experience relates to the formulation, implementation, evaluation and formulation of regiional plans for agriculture statistics, marketing, livestock, irrigation, fisheries, forestry, wildlife, national parks, tourism, agro-industrial and social sectors like demography, health
Keywords: IES as an author (Indian Economic Service); Agriculture-India-Bihar